EFEKTIVITAS PROGRAM KAKAO LESTARI DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT PADA DESA NUSASARI KABUPATEN JEMBRANA - Kristina, Angel Maria; Yudharta, I Putu Dharmanu; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
The cocoa farming commodity in Indonesia is very high, as a country with the 5th largest cocoa producer in the world, Indonesia can provide a global market so that it can help increase economic income. The increase in the economy greatly affects the welfare of the community. Today one of the problems of public welfare is poverty. Jembrana Regency as one of the largest cocoa plantation producers in Bali is experiencing poverty problems, especially in Nusasari Village with the use of Cocoa Natural Resources so the Cocoa Lestari program is formed. The Cocoa Lestari Program certainly has various problems in its implementation process and its effectiveness is very important. This study discusses the effectiveness of the sustainable cocoa program in improving the welfare of Nusasari Village. This study uses a descriptive qualitative method. Keywords: Effectiveness, Sustainable Cocoa Program, Nusasari Village